Selenio : metabolismo y suplementación en el paciente crítico (2007)
ABSTRACT: Critical patients are especially vulnerable to deficit of nutrients, because of the hyper metabolic condition, activates some catabolic processes that lead patients to have low plasmatic levels of specific nutrients and increased requirements of them, which, cannot be meet with formulas of standard nutrition. One of the nutrients affected is selenium, indispensable to the formation of selenoproteins that are essential to the function of reducing enzymes such as glutathione peroxidase and is needed to stimulate antioxidant functions. This review summarizes some studies and clinical trials about the use of selenium supplement to increase plasma levels that could improve health parameters in patients with sepsis, burn and trauma. But until now the components in selenium that improve metabolic functions and the mechanisms by which selenium exert immune an antioxidant effects are still far from fully understood. To confirm the scientific basis of the selenium supplementation, there is a need to keep on systematizing newly obtained scientific data on selenium.